Origin of Permian OIB-like basalts in NW Thailand and implication on the Paleotethyan Ocean - Yuejun Wang (2018)
© 2016 Elsevier B.V. The basaltic rocks in NW Thailand belong to part of giant Southeast Asian igneous zone that delineates the extension of the Paleotethyan Ocean from SW China into NW Thailand. The Chiang Mai basaltic samples from the Chiang Dao, Fang, Lamphun and Ban Sahakorn sections are divisible into two groups of high-iron basalt. Group 1 has SiO2of 38.30–49.18 wt.%, FeOt of 13.09–25.37 wt.%, MgO of 8.38–1.60 wt.%, TiO2of 3.92–6.30 wt.%, which is rarely observed in nature. Group 2 shows SiO2 = 44.71–49.21 wt.%, FeOt = 10.88–14.34 wt.%, MgO = 5.24–16.11 wt.%, TiO2 = 2.22–3.07 wt.% and mg# = 44–70. Olivine and pyroxene are responsible for the fractionation of the Group 2 magma whereas low oxygen fugacity during the late-stage differentiation of the Group 1 magma prolonged fractionation of ilmenite and magnetite. The onset of ilmenite and magnetite fractionations controls the distinct differentiation commencing at MgO = ~ 7 wt.%. Both groups show similar REE and primitive mantle-normalized patterns with insignificant Eu, Nb-Ta and Zr-Hf anomalies. They have similar Nd isotopic compositions with εNd(t) values ranging from + 2.8 to + 3.7 and similar Nb/La, Nb/U, Th/La, Zr/Nb, Th/Ta, La/Yb, Nb/Th, Nb/Y and Zr/Y, resembling those of OIB-like rocks. The representative basaltic sample yields the argon plateau age of 282.3 ± 1.4 Ma, suggestive of Early Permian origin. Our data argue for Group 1 and Group 2 are coeval in the intra-oceanic seamount setting within the Paleotethyan Ocean, which at least continued till 283 Ma. These data, along with other observations, suggest that the Inthanon zone defines the main Paleotethyan suture zone, which northerly links with the Changning-Menglian suture zone in SW China.